Health Infrastructure and Economic Growth in Sub-Saharan Africa - Lamptey, Richmond; Adams, Samuel; Mensah Klobodu, Edem (Health Economics and Healthcare Reform : Breakthroughs in Research and Practice, 2018)
The effective delivery of healthcare services is vital to the general welfare and well-being of a country’s citizens. Financial infrastructure and policy reform can play a significant role in optimizing existing healthcare programs. Health Economics and Healthcare Reform: Breakthroughs in Research and Practice is a comprehensive source of academic material on the importance of economic structures and policy reform initiatives in modern healthcare systems. Highlighting a range of pertinent topics such as clinical costing, patient engagement, and e-health, this book is ideally designed for medical practitioners, researchers, professionals, and students interested in the optimization of healthcare delivery.